Comparing Norse animal husbandry practices: paleoethnobotanical analyses from Iceland and Greenland - Ross, Julie; Zutter, Cynthia (My University, 2007)
The popular view of the Norse settlement across the North Atlantic describes colonies with similar subsistence practices being established from the Faroe Islands in the west to L'Anse aux Meadows in the east. The importance of plant resources to the Norse animal husbandry strategies implemented by settlers upon arrival are not well established, nor are the changes these strategies underwent, eventually resulting in different cultural solutions to varying environmental and social factors. This paper compares archaeobotanical samples from two Icelandic archaeological sites, Svalbarð and Gjögur, and one Greenlandic site, Gården Under Sandet (GUS). Results of this comparison suggest that heathland shrubs were an important fodder resource for caprines in both Iceland and Greenland while apophytes ('weedy taxa') were part of the cattle fodder in Greenland. Further, the results indicate that mucking out of cattle barns to provide fertilizer was likely practiced at the GUS site in the Western Norse settlement of Greenland.
Keywords: animal remains; plant remains; archaeobotany